Novel fat suppression technique for ultrashort echo time MRI using single-point Dixon phase modeling - Newbury, Nathan; Sedaghat, Sam; Athertya, Jiyo S.; Shin, Soo Hyun; Ma, Yajun; Jerban, Saeed; Carl, Michael; Silva, Melissa Lou; Chang, Eric Y.; Du, Jiang; Jang, Hyungseok (Quantitative imaging in medicine and surgery, 2025)
Background: Fat suppression plays a vital role in numerous magnetic resonance imaging (MRI) examinations, particularly in the musculoskeletal (MSK) system. However, current fat suppression methods are not fully optimized for ultrashort echo time (UTE) imaging, despite being essential for many advanced UTE-based imaging applications. This study aimed to investigate a novel fat suppression technique for UTE MRI using a single-point Dixon (1p-Dixon) approach through phase modeling. Methods: In this study, four cadaveric human knee joints, and six healthy volunteers were included. A1p-Dixon-based fat suppression method was developed, which utilizes intrinsic information from complex UTE signals. Additionally, a data-driven approach based on the phase distribution was used for the decomposition of water and fat signals in short T2 tissues. The feasibility of the proposed method was evaluated in a fat-water phantom first and validated in ex vivo and in vivo human knee joints. The patellatendon, cartilage, posterior cruciate ligament (PCL), anterior cruciate ligament (ACL), and meniscus were evaluated in each knee. Results: In the phantom experiment, there was a significant correlation between the estimated fat fraction and the actual fat fraction (R>0.98; P<0.05). The ex vivo experiment revealed a significant difference in contrast-to-noise ratios (CNRs) measured from the two images without and with 1p-Dixon (P<0.001).The CNR values ranged from 3.4±0.5 to 9.6±5.0 and 1.8±1.6 to 4.1±0.8 for measurement with and without 1p-Dixon, respectively. The 1p-Dixon significantly improved the contrast in the in vivo experiment (P<0.0001). The CNR values ranged from 5.1±6.0 to 41.0±9.7 and 2.7±1.2 to 15.4±3.3 for measurement with and without 1p-Dixon, respectively in the in vivo experiment. Conclusions: Our novel fat suppression technique has been shown to provide a fast, time-saving, and robust fat suppression for UTE imaging without the need for need for additional scans.